A Randomized Control Trial of Cognitive Compensatory Training (CCT) and Computerized Interactive Remediation of Cognition-Training for Schizophrenia (CIRCuiTS) - Dark, Frances Louise; Gore-Jones, Victoria; Newman, Ellie; Wheeler, Maddison; Demonte, Veronica; Northwood, Korinne (Frontiers in Psychiatry, 2022)
Background: Various modes of delivering cognitive remediation (CR) have been found to be effective but there have been few head-to-head trials of different approaches. The aim of this trial was to evaluate the relative effectiveness of two different programmes, Cognitive Compensatory Training (CCT) and Computerised Interactive Remediation of Cognition – Training for Schizophrenia (CIRCUiTs). Methods: The study used a single blind randomised, controlled trial to examine the efficacy and effectiveness of the two therapies. The study aimed to recruit 100 clinically stable patients, aged between 18 and 65 years with a diagnosis of a Schizophrenia spectrum disorder. Participants were randomised to either the CCT or CIRCUiTs therapy groups. The primary outcome measures were, neurocognition using the Brief Assessment of Cognition Scale (BACS), and the Subjective Scale to Investigate Cognition in Schizophrenia (SSTICS). The secondary measure was functional outcomes using the Social Functioning Scale (SFS). Results: There was no group difference on any of the outcome measures post intervention or at follow up. Both groups had a small improvement on their SSTICS scores between Baseline (M = 30.52, SD = 14.61) and Post-Intervention (M = 23.96, SD = 10.92). Verbal memory scores improved for both groups between Baseline (M = -1.61, SD =1.06) and 3-month Follow-up (M = -1.00, SD = 1.00). Discussion: This under powered study found no difference in effect between the two approaches studied. If future studies confirm this finding, then it has implications for services where cost and lack of computer technology could pose a barrier to addressing the cognitive domain of schizophrenia spectrum disorders. The final sample size compromised the power of the study to conclusively determine significant effect.